Desi poultry integration in litchi orchard for enhancing farmer’s income - Singh, Sanjay Kumar; Kumar, Pankaj; Nath, Vishal; Pandey, S D (Indian Horticulture, 2023)
Litchi (Litchi chinensis Sonn.) is one of the major commercial fruit crops of Northern India. Litchi orchards are the main source of income for the farmers who used to care for orchard themselves or give orchard to pre-harvest contractors. One developed orchard of litchi can give net profit up to ` 2.0-2.50 lakhs per ha but integration of desi birds in litchi orchard ecosystems can help to enhance farmer’s income further through organic fruit production. Looking for an organic method of reducing insect-pests in litchi orchard and enhanced soil fertility [due to poultry litters], poultry rearing can be considered as an option. There are many benefits to letting chickens roam around litchi orchard. These birds can help us to manage both weeds and insects without the use of pesticides, while also naturally fertilizing orchard soil. Poultry eggs are additional benefits. The article highlights the main details concerned with litchi orchard based desi poultry farming system.